Adult Attachment, Emotional Intelligence and Depression among Low Rank Police Officers (International Journal of Psychosocial Rehabilitation, 2020)
The study was aimed to examine the relationship between adult attachment and emotional intelligence and depression among low-rank police officers in Sarawak Contingent Police Headquarters. A correlational research design with a quantitative method and random sampling was adopted in this study. Three instruments were used in this study: Experience in Close Relationship (ECR), Self-Report of Emotional Intelligence Scales, and Depression – Happiness Scales. About 250 low-ranking police officers, 171 men and 79 women, participated in this study. Analysis of variance was used to estimate the adult attachment emotional intelligence scores as associated with depression. The types of adult attachment were tested as a moderator in the association between emotional intelligence and depression. The finding indicated that emotional intelligence was significantly associated with depression (r = .165, p < .010). Depression has shown not to be significantly associated with attachment avoidance (r = -.057, p = .552) but significantly associated with anxiety (r = .287, p < .010). The finding suggested that emotional intelligence plays a more important role in controlling participants’ level of depression compared to adult attachment.